2019
DOI: 10.1002/ird.2396
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CANAL AUTOMATION ON REDUCING GROUNDWATER EXTRACTION WITHIN IRRIGATION DISTRICTS: CASE STUDY OF QAZVIN IRRIGATION DISTRICT

Abstract: The impact of upgrading irrigation canal water distribution and delivery systems on reducing the pumping of water from aquifers was investigated. Consequently, energy consumption and carbon emission reduction were investigated. For this purpose, a decentralized integrated control system and a centralized control system were designed. The arrangements were tested on the main canal of the Qazvin Irrigation District under a water shortage scenario. In this research, the centralized automatic control system was sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They found that the reinforcement learning-based proportional-integral controller tuning method outperformed both integer and fractional order proportional-integral controllers. The effects of canal automation on the improvement of water distribution and delivery systems of irrigation canals were investigated [26]. For this purpose, a decentralized and a centralized control system were designed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the reinforcement learning-based proportional-integral controller tuning method outperformed both integer and fractional order proportional-integral controllers. The effects of canal automation on the improvement of water distribution and delivery systems of irrigation canals were investigated [26]. For this purpose, a decentralized and a centralized control system were designed.…”
Section: Introductionmentioning
confidence: 99%
“…Mismanagement of surface water distribution in many agricultural districts has led to an uncertain and unstable agricultural water supply (Babaei et al, 2018;Hashemy et al, 2018). This has led to a growing tendency of farmers to supply agricultural water from groundwater sources, including environmental problems such as the unauthorized withdrawal of static aquifers (Hosseini Jolfan et al, 2019), subsidence of agricultural plains, the decline in groundwater quality (Fard et al, 2021), salinization and waterlogging, soil erosion, and pollution of rivers and lakes (Monem & Hashemy, 2011). Therefore, upgrading the current agricultural water management to increase sustainable production of food products with minimum water loss is essential for reliable development in agriculture.…”
mentioning
confidence: 99%